Катюша. У смерти женское лицо: [роман] / М. Воронина - Воронина Марина Николаевна (Современный литератор, 1999)
Экземпляры: ф.1 (2003) / Инвентарный номер: 45549 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 75 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44